Color atlas and synopsis of clinical dermatology common and serious diseases - Fitzpatrick, Thomas B.; Johnson, Richard Allen; Wolff, Klaus (New York : McGraw-Hill, 2001)
Instant access to more than 680 exceptional vivid color photographs of all common and uncommon diseases
CD-ROM Version 2.0
System requirements: Recommended system requirement; 16-bit color (thousands of colors) or greater video subsystem, 24 MB RAM, PowerPC (Mac) or Pentium (Windows) processor
System requirements: Minimum system requirements; 8-bit color (256 colors) video subsystem, 16 MB RAM, PowerPC (Mac) or Pentium (Windows) Processor, 10 MB of available hard-disk space, Mac OS software version 7.1.2 or later OR Microsoft Windows 95, or Windows NT 4.0 with service Pack 3 or later
Keywords: Dermatology -- atlases; Skin Diseases -- atlases